Spatial Map of Geohelminths Infection in Agricultural Communities and its Contamination in Soil of Jatian Village, Jember Regency - Yunita Armiyanti; Nanda Nuramna; Muhammad Afiful Jauhani; Bagus Hermansyah; Wiwien Sugih Utami (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Geohelminth infections are a neglected global health problem. Data from the World Health Organization (WHO) in 2020 show that more than 24% of the world population is infected by geohelminths. The condition of the agricultural soil, which tends to be loose and moist, supports the development of the infective form of the geohelminth. This makes agricultural communities susceptible to geohelminth infections. This study aimed to determine a spatial map of geohelminth infection in agricultural communities and its contamination in the soil of Jatian Village, Jember Regency. Methods: This study used an observational analytical design and a spatial analysis approach. Sampling was performed using a random sampling method that included 43 samples. Data were obtained by examining soil and stool samples and the coordinates of the sampling locations. Data were analyzed using spatial analysis. Results and Discussion: The results of this study indicated that the prevalence of geohelminth infection in agricultural communities was 23.3%, and its contamination in the soil was 6.98%. Hookworms caused infections among respondents, and contamination in the ground was caused by Hookworms and Strongyloides stercoralis. Clustering analysis results showed that geohelminth infection formed two secondary clusters. Spatial autocorrelation and buffer analysis showed clustering of geohelminth infections within the buffer range (<100 m), indicating that the infection spreads more easily within the cluster. Conclusion: The spatial map showed the distribution pattern of clustered geohelminth infection cases and their contamination in soil within proximity, thereby increasing the risk of geohelminth transmission.